Pengaruh Perbedaan Ukuran Mata Jaring (Mesh Size) pada Alat Tangkap Jaring Insang (Gill Net) Terhadap Hasil Tangkapan Nelayan di Grajagan, Banyuwangi, Jawa Timur - Dhea Ananda; Yusrudin Yusrudin; Sumaryam Sumaryam (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2026)
The fishing gear operated by fishermen along the coast of Grajagan Beach to catch fish is a bottom gill net, using different mesh sizes of 3, 4, and 6 inches. The method used in this study was the Experimental Fishing method, which involved direct observation over nine repetitions using different mesh sizes. Observations were conducted on the quantity of fish caught, and direct interviews were carried out with fishermen regarding the use of gill nets at Grajagan Beach, Banyuwangi, East Java. The composition of the catch showed that the largest proportion by weight was shovel-nosed ray, accounting for 15%, while lobster represented the highest number of individuals caught, at 12%. To determine whether there was an effect of mesh size on the catch yield, an ANOVA test was conducted and produced significant results, indicating that differences in mesh size significantly influenced the catch. In this study, a follow-up (Post Hoc) test was also performed using Tukey’s Honest Significant Difference (HSD) test. The results of the post hoc test showed that the use of a 6-inch mesh size had a substantial effect on the catch yield.